Pengaruh berbagi informasi terhadap kualitas produk yang dimediasi oleh keselarasan kualitas: Studi pada Kedai Kopi di Kabupaten Sleman, D. I. Yogyakarta - Kalam, Fatahillah Akbar; Kusmantini, Titik; Ediningsih, Sri Isworo (Journal of Business and Information Systems (e-ISSN: 2685-2543), 2019)
The purposes of this research are to determine the effect of Information Sharing and Product Quality with the mediation of Conformance Quality. The type of this research is observatory research, with a quantitative method approach. The research took place at Sleman, Yogyakarta. The size of the samples 65 coffee shops. The sampling technique uses convenience sampling. The data analysis techniques used in this research are path analysis and linear regression. The results of this research show that there is a significant effect of information sharing and conformance quality on product quality. There is a significant effect of information sharing on conformance quality. There is a significant effect of conformance quality as the mediation of information sharing and product quality. The result of this research demonstrated there is an effect on each other variables.